PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI DI DINAS PETERNAKAN DAN PERTANIAN KABUPATEN KUTAI TIMUR - Ludia Rura Fl. Sudiran (ADMINISTRASI PUBLIK, 2017)
This study aims to find the effect of job satisfaction on employee commitment in the Livestock and Agriculture East Kutai, therefore the researchers to formulate hypotheses "Allegedly job satisfaction have an influence on the commitment in the Livestock and Agriculture Kutai Timur".The timing of the research was conducted in September 2016 until the month of December 2016 for 3 (three) months. The research method in this study is quantitative, the data obtained through direct observation in the field and distributing questionnaires to the speakers with a sample size of 15 (fifteen) respondents.Based on the calculation of Product Moment Correlation is known there is a correlation between job satisfaction with the commitment of employees with the number 0.714. This figure is interpreted as a very strong correlation between job satisfaction with employee commitment.While testing the hypothesis generating empirical rxy figure of 0.714 where r xy table for N = 15 (with a 95% confidence level) is 0.541, then the empirical rxy> r xy table. Thus it can be said that there is a positive relationship between job satisfaction variable (X) and the commitment variable (Y) employees in the Department of Animal Husbandry and Agriculture East Kutai.